Effect of vegetable oils with different fatty acid composition on high-fat diet-induced obesity and colon inflammation - Thomas, Shalom Sara (Nutr Res Pract, 2020)
BACKGROUND/OBJECTIVES: Different fatty acids exert different health benefits. This study investigated the potential protective effects of perilla, olive, and safflower oils on high-fat diet-induced obesity and colon inflammation. MATERIALS/METHODS: Five-week old, C57BL/6J mice were assigned to 5 groups: low-fat diet (LFD), high-fat diet (HFD) and high-fat diet supplemented with-perilla oil (HPO), olive oil (HOO), and safflower oil (HSO). After 16 weeks of the experimental period, the mice were sacrificed, and blood and tissues were collected. The serum was analyzed for obesity- and inflammation-related biomarkers. Gene expression of the biomarkers in the liver, adipose tissue, and colon tissue was analyzed. Micro-computed tomography (CT) analysis was performed one week before sacrifice. RESULTS: Treatment with all the three oils significantly improved obesity-induced increases in body weight, liver weight, and epididymal fat weight as well as serum triglyceride and leptin levels. Treatment with perilla oil (PO) and safflower oil (SO) increased adiponectin levels. The micro-CT analysis revealed that PO and SO reduced abdominal fat volume considerably. The mRNA expression of lipogenic genes was reduced in all the three oil-supplemented groups and PO upregulated lipid oxidation in the liver. Supplementation of oils improved macroscopic score, increased colon length, and decreased serum endotoxin and proinflammatory cytokine levels in the colon. The abundance of Bifidobacteria was increased and that of Enterobacteriaceae was reduced in the PO-supplemented group. All three oils reduced proinflammatory cytokine levels, as indicated by the mRNA expression. In addition, PO increased the expression of tight junction proteins. CONCLUSIONS: Taken together, our data indicate that the three oils exert similar anti-obesity effects. Interestingly, compared with olive oil and SO, PO provides better protection against high-fat diet-induced colon inflammation, suggesting that PO consumption helps manage inflammation-related diseases and provides omega-3 fatty acids needed by the body.